Performance analysis of working with relational and non-relational databases in Java applications - Krzysztof Caban; Paweł Czuchryta; Beata Pańczyk (Journal of Computer Sciences Institute)
The article presents a performance analysis of connections to both relational and non-relational databases, critical components of the functionality of modern web applications. The study is concerned with evaluating the advantages of manually integrated database drivers compared to the comprehensive Spring Data module. In addition, the impact of the Spring Framework on the performance of drivers responsible for database connections was investigated. Based on the results obtained, there are performance benefits for CRUD operations when adding drivers manually and using the Spring Framework for JDBC and MongoDB drivers.